The milk fat globule size governs a physiological switch for biofilm formation by Bacillus subtilis - Raz, Chen; Paramonov, Margarita Maggie; Shemesh, Moshe; Argov-Argaman, Nurit (Frontiers in Nutrition, 2022)
Milk lipids are organized in the form of milk fat globules (MFG), ranging in size from 0. 1 to 15 μm. The MFG size is closely associated with the composition of fatty acids, polar lipids, sphingolipids, cholesterol and the content of the MFG membrane (MFGM). Also, the MFGM integral proteins and glycoconjugates differ in composition and structure between different MFG size groups. These compositional differences may modulate the functionality of the MFG and its interaction with microbial cells. We report that small (2.3 μm) MFG facilitates the growth of the Gram-positive bacterium Bacillus subtilis whereas induction of biofilm formation was found in the presence of large (7.0 μm) MFG. Attempting to distinguish between the role played by the size from that played by the composition of the MFG, we compared phospholipid composition between treatments. We found that adjusting the phosphatidylethanolamine (PE) level to the concentration found in the small MFG, increased growth but suppressed biofilm formation in the presence of large MFG. The same normalization protocol for phosphatidylinositol (PI) or sphingomyeline (SM) did not exert a similar effect, suggesting a specific role for PE in regulating bacteria proliferation. We suggest that the content of MFGM, affected by MFG size, governs the ability of B. subtilis to utilize lipids from milk fat. This process might affect the bacterial decision-making toward biofilm formation or growth.